Paris polyphylla in Dibang Valley District, Arunachal Pradesh: Need for an Integrated Conservation Program in the Eastern Himalayan Biodiversity Hotspot - Adhikarimayum, A. S.; Mihu, Ayome; Rawat, G. S.; Gopi, G. V. (Indian Forester, 2020)
No Abstract.